2017
DOI: 10.1002/nbm.3861
|View full text |Cite
|
Sign up to set email alerts
|

Online 1H‐MRS measurements of time‐varying lactate production in an animal model of glioma during administration of an anti‐tumoral drug

Abstract: The aims of this study were to implement a magnetic resonance spectroscopy (MRS) protocol for the online profiling of subnanomolar quantities of metabolites sampled from the extracellular fluid using implanted microdialysis and to apply this protocol in glioma-bearing rats for the quantification of lactate concentration and the measurement of time-varying lactate concentration during drug administration. MRS acquisitions on the brain microdialysate were performed using a home-built, proton-tuned, microsolenoid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…The enzyme lactate dehydrogenase (LDH) was also blocked with oxamate to assess the implication of lactate metabolism in the neuroprotection. 42 , 43 Motor and behavioral studies were also carried out to evaluate the long-term effect of lactate injection on cognitive functions. Our results demonstrate that both exogenous and endogenous lactate exert a neuroprotective effect on neonatal HI insult and open the way to clinical trials in the future, as already ongoing in human adult TBI.…”
Section: Introductionmentioning
confidence: 99%
“…The enzyme lactate dehydrogenase (LDH) was also blocked with oxamate to assess the implication of lactate metabolism in the neuroprotection. 42 , 43 Motor and behavioral studies were also carried out to evaluate the long-term effect of lactate injection on cognitive functions. Our results demonstrate that both exogenous and endogenous lactate exert a neuroprotective effect on neonatal HI insult and open the way to clinical trials in the future, as already ongoing in human adult TBI.…”
Section: Introductionmentioning
confidence: 99%
“…This time lag corresponds to the time required for the dialysate to travel the distance from the microdialysis membrane to the NMR microsolenoid. Measurement of this transit time was reported in a previous study (Crémillieux et al, 2018). This increase in lactate was observed in five consecutive spectra, a time window that corresponds ~15 min whisker stimulation period.…”
Section: Resultsmentioning
confidence: 84%
“…In a recent study (Crémillieux et al, 2018), we showed that, in the absence of macromolecules and lipids in the microdialysate, an accurate determination of lactate levels both in a glioma and in the healthy brain could be obtained online using a sensitive NMR microcoil. In this previous study the detection and quantification of lactate was, however, performed under isoflurane anesthesia, which is known to highly increase brain lactate concentration (Horn and Klein, 2010).…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…During the long acquisition time, several metabolites (such as lactate) may be detected inappropriately due to the dynamic nature of metabolic processes in vivo since MRS detects steady-state metabolite levels instead of real-time production and excretion rate. 50,51 Therefore, methods such as two-dimensional wavelet encoding-spectroscopic imaging have been proposed to shorten the acquisition time and reduce voxel size. 52 MRS has considerable potential to evaluate metabolism in tumors, and efforts are underway to improve its quantitative accuracy and correct for other factors affecting assessment accuracy.…”
Section: H Magnetic Resonance Spectroscopymentioning
confidence: 99%